Cerebrospinal fluid analysis of pregnant women at early stages of COVID-19 - Lizandra Paravidine Sasaki; Geraldo Magela Fernandes; Angelo Pereira da Silva; Felipe Motta; Clara Siracusa; Isadora Pastrana Rabelo; Agenor dos Santos Junior; Paulo Sergio França; Patricia Kurisky; Rosana Maria Tristao; Cleandro de Albuquerque; Ciro Gomes; et al. (Elsevier, 2022)
Objective: To determine the presence or absence of SARS-CoV-2 in the cerebrospinal fluid of pregnant women at early stages of COVID-19. Materials and methods: We conducted a prospective observational study with pregnant women undergoing cesarean section and real-time polymerase chain reaction to SARS-CoV-2 was performed in the cerebrospinal fluid in the early stages of COVID-19. Results: Fourteen pregnant women, whose COVID-19 symptoms started between four to 18 days prior to delivery, were included. Eleven of the women reported anosmia, dysgeusia, and headaches and there were two fatal cases. SARS-Cov-2 was not present in the cerebrospinal fluid of these COVID-19 patients with early neurological symptoms, even in severe cases. Conclusion: Our study suggests that peripheric cell damage and parainfectious phenomena may predominate over direct central nervous system injury in the pathophysiology of COVID-19 related early neurological symptoms on pregnant women.